EARLY VERSUS DELAYED ORAL INTAKE IN PATIENTS AFTER CESAREAN SECTION UNDER REGIONAL ANESTHESIA: Early Versus Delayed Oral Intake - Hassan, Laiqa; Tufail, Shazia; Aslam, Farheen; Mustafa, Nilofar; Ahmed, Arub; Qamar, Saima (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the outcome in early versus delayed oral intake in patients after cesarean section under regional anesthesia. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital Lahore, from Dec 2017 to May 2018. Methodology: A total of 352 women undergoing elective cesarean section under regional anesthesia, nil by mouth for at least 8 hours before surgery were divided in 2 groups. In group 1, patients were given sips of clear oral fluid (water) <5 hours after cesarean section and in group 2, patients received sips of water 8 hours following surgery. Bowel motility was assessed after surgery on hourly basis. Data about time interval to first bowel movement and ileus were noted. Results: Mean age of patients was 32.329 ± 3.44 years and 33.051 ± 3.64 years in group 1 and 2 respectively. Mean gestational age and body mass index was 38.50 ± 0.93 weeks and 29.824 ± 4.97 kg/m2 in group-1 versus 37.937 ± 0.98 weeks and 27.779 ± 2.81 kg/m2 in group 2. Mean duration of surgery was 47.096 ± 6.65 minutes in group-1 and 47.647 ± 8.76 minutes in group 2. Ileus was seen in 17% patients in group-1 and 34.1% in group-2 (p<0.001). Mean time interval for first bowel movement was 8.323 ± 1.20 hours in group-1 and 13.034 ± 2.54 hours in group 2 (p<0.001). Conclusion: Early feeding after an uncomplicated cesarean section has reduced rate of ileus symptoms and mean time interval for bowel......